A Norma STEP - ISO10303 AP242 como Instrumento de Integração entre Engenharia de Produto e de Processo - Miguel Ângelo Jesus Vidal Ribeiro (2016)
The companies that make custom products are constantly required to provide a considerably high number of price estimates based on 2D or 3D drawings, being that the great majority of them are 2D type in PDF format. In order to give the customer a quote we have to extract from the drawings the material requirements, necessary operations and resources. This task requires the utmost attention, care and is time consuming. Most Computer Aided Design (CAD) systems are capable to export 3D models in STEP format, an ISO standard. This format allows us to extract geometry information and the assembly structure of an product. The use of 3D models exported in STEP format also allows us to narrow the "gap" that exists between product and process engineering. The STEP AP242 standard is now being adopted and implemented by the major 3D CAD systems manufacturers, yet the tools that manipulate these STEP models and use their potential from the point of view of integrating project and process engineering are still rare, incomplete and overly expensive. The aim is to develop a simple and accessible tool that allows efficient integration between design and manufacturing stages. This tool will consist of a web service, that extracts from a STEP file the product assembly structure and geometry information of an item to produce, and a simple web based viewer that visualizes the components as we navigate in the product assembly structure previously imported.